2021
DOI: 10.1016/j.jhtm.2021.07.016
|View full text |Cite
|
Sign up to set email alerts
|

Community eco-tourism in rural Peru: Resilience and adaptive capacities to the Covid-19 pandemic and climate change

Abstract: The recent outbreak of COVID-19 has been devastating for international tourism, adversely affecting destinations, organizations, and local communities. In particular, the crisis highlights the need for local communities reliant on rural tourism to enhance their resilience to the risks simultaneously generated by the pandemic and accelerating impacts of climate change. This is important as the effects of these hazards are intertwined and cannot be treated in isolation. We explore community responses and resilie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
43
0
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 80 publications
(74 citation statements)
references
References 57 publications
(64 reference statements)
2
43
0
3
Order By: Relevance
“…This result is opposite to Roman et al [70], who found agritourism was the main attraction during COVID-19 in Poland. If community homestays are well prepared by bonding through social networks and conveying a message that they are ready and willing to host tourists, they can overcome such a crisis [92]. Rural destinations, including rural villages and travel motivation, had a significant connection (5%) and 4th contributor in marginal effects calculation.…”
Section: Resultsmentioning
confidence: 99%
“…This result is opposite to Roman et al [70], who found agritourism was the main attraction during COVID-19 in Poland. If community homestays are well prepared by bonding through social networks and conveying a message that they are ready and willing to host tourists, they can overcome such a crisis [92]. Rural destinations, including rural villages and travel motivation, had a significant connection (5%) and 4th contributor in marginal effects calculation.…”
Section: Resultsmentioning
confidence: 99%
“…The practical implications of the rural tourism evolution, however, are complex, largely due to its dynamic and multifaceted nature [6,36]. Tourism activity, in essence, demands direct and indirect connections between different sectors of the economy [28], such as restaurants, construction, and artisanal productions [1].…”
Section: Literature Review 21 Community-based Rural Tourism (Crt)mentioning
confidence: 99%
“…However, the closing of borders in an effort to contain the COVID-19 pandemic has seriously impacted the sector, reducing the number of travelers around the world by 60-80% [1,5]. As a result, individuals and organizations faced the challenge of reinventing and optimizing their operations, seeking new strategies to adapt to a temporarily collapsing market [1,6]. In this context, as international borders remained closed and the desire to travel increased after months of social distancing, rural destinations became an attractive option, especially for domestic tourists [7,8].…”
Section: Introductionmentioning
confidence: 99%
“…Community resilience exists as an interaction between individuals and their communities, determining the success of the community in meeting the needs of members in dealing with crises (Kimhi et al 2020) including during COVID-19 (Rippon et al 2020). During the pandemic, community resilience was quite successful in building a situation to face a crisis, such as what happened in community eco-tourism in rural Peru (Gabriel-Campos et al 2021), community nurses in Massachusetts (Baughman et al 2021), the newspaper community in the United States (Finneman et al 2021), and community pharmacy in Ontario Canada (Austin & Gregory 2021). In this context there was a role for local government as in the United States (Entress et al 2020) and the United Kingdom (South et al 2020) It is important that in terms of the elderly in China, the elderly's high trust in the government allowed them to be calmer in dealing with the pandemic (Zhang et al 2021).…”
Section: Introductionmentioning
confidence: 99%